Typification of Opuntia australis (Cactaceae) with an original plate from 1882 and history of the plant's finding - Kiesling, Roberto (2021)
The neotypification of Opuntia australis F.A.C.Weber, basionym of Pterocactus australis (F.A.C.Weber) Backeb., is made here thanks to the discovery of Weber?s personal notes about it, and of two notebooks containing respectively a drawing and a short description of that plant, both made at the time of its first collection in 1882. Outlined as well is the poorly documented scientific expedition that made this first discovery and the cultivation of an early plant by F.E. Schlumberger on Weber?s behalf. A Weber?s note confirms he knew the mentioned illustration. A herbarium specimen from the same gathering has been found, but it cannot be considered original material since there is no evidence that it was seen by Weber. However, this specimen is here designated as epitype.